Gamification of Academic Integrity: Reviewing an Evaluation Tool - Khan, Zeenath Reza; Sivasubramaniam, Shivadas; Gomes, Sandra F.; Bjelobaba, Sonja; Razi, Salim; Waddington, Lorna; Ribeiro, Laura (Canadian Perspectives on Academic Integrity, 2021)
Gamification and game-based learning have been around since 2008 and have become more important by the 2015s. Academics and educators, whether in the educational sector or professional development in the corporate world, recognise the many benefits of either using game-based learning or gamifying learning modules because they bring about greater engagement from participants, allow for knowledge retention and skills acquisition through practice immersion and so on. The European Network for Academic Integrity formed a working group in 2019 to look at the gamification of “academic integrity” and to support the greater community in this matter. Consisting of multidisciplinary, multinational members, the group actively works towards knowledge building, capacity building and ultimately proposing a multitude of resources that can help educators everywhere in training and raising awareness on academic integrity by means of gamification. In its first year of formation, the group looked at preliminary stages of developing a gamified module on academic misconduct, particularly contract cheating, having developed a database of possible scenarios from experiences shared by members and during a workshop run at a conference. The group also published a paper on the steps to follow up to the design stage of developing such modules (Khan et al., 2021). The group is now actively working towards identifying and reviewing existing games and/or gamified modules that are currently being used globally towards teaching, training or raising awareness on academic integrity, integrity values, ethics, morals, and professional codes of conduct. In doing so, the group has identified many rubrics to be used to review games and gamified modules. The initial list of 18 items were proposed based on literature review (All et al., 2014; Stewart, 2015; “Brainpop Educators”, 2015; “California State University”, 2007; Gilliver-Brown & Ballinger; 2017; “Union-Endicott Central School District”, 2021) which followed a period of pilot testing of the identified rubric items by the group members. A virtual meeting among the members then led to revising, rewording, removing, and adding items based on the experience of using the 18 items previously identified. This contributed to the establishment of content validity of the rubric and resulted in a total of 21 items being identified by the group for further testing (see Table 1 below). Table 1 - Proposed and Intended items making up a rubric to review and assess effectiveness of a game or gamified learning module Item # Proposed Item Intended questions 1 Relevance to academic integrity Is there relevance to academic integrity 2 Problem solving characteristics/ higher level learning skills Does the game incorporate problem-solving characteristics/ higher level learning skills 3 Integrated content to game play Removed as this would only be appropriate at a later stage of development 4 Knowledge content Does the game prompt player to think critically about AI 5 Relation of game content and control to student knowledge and ability Is game applicable universally (target group) 6 Usability (user friendliness of instructions) Are game instructions user friendly 7 Usability (user friendliness of interface) Is the interface user friendly 8 Design and artwork (creativity) Is the design and artwork attractive 9 Interactivity of user/ Immersion Did you enjoy the game 10 Embedded assessment Does the game have assessments to test content knowledge 11 Audio Audio quality 12 Narrative and Theme Effectiveness of story telling 13 Pedagogical Value (goals) Are the goals of the game clear 14 Browser/device compatible Browser/device compatibility 15 Available languages Is game available in multiple languages 16 Supporting material Quality of supporting material 17 Diversity Is game applicable universally (inter-culture) 18 Feedback Is feedback on player performance suitable 19 *Possible assessments Should the game rank players performance 20 *Scenarios for assessments Should player ranking be time-based 21 *Interdisciplinary applicability Is game applicable universally (inter-discipline) 22 *Resource needs Is technical support suitable * items added after the pilot testing In this presentation, the group will introduce gamification and game-based learning, the importance of these techniques when it comes to academic integrity and provide an overview of the work done so far. It will also introduce the 21 rubrics that were originally used for developing game-based approaches to teach academic integrity; with the intention to lead a discussion with the audience and collect feedback on the relevance and appropriateness of the items when reviewing games and gamified modules.